Hapten sensitization to vaginal mucosa induces less recruitment of dendritic cells accompanying TGF‐β‐expressing CD206+ cells compared with skin. Issue 4 (10th March 2022) - Nakayama, Kanako; Nishijo, Taku; Miyazawa, Masaaki; Watabe, Tetsuro; Azuma, Miyuki; Sakaguchi, Hitoshi
Abstract: Introduction: Contact hypersensitivity (CHS), a type of delayed‐type hypersensitivity, is induced by hapten exposure to the skin and mucosa. We previously reported that, in a murine model of CHS, the vaginal mucosa (VM) sensitization showed lower T‐cell responses as compared with the abdominal skin sensitization. To investigate mechanisms of impaired CHS by the VM sensitization, we compared migration of hapten‐captured dendritic cells (DCs) in the draining lymph nodes (dLNs) and recruitment of DCs at the sensitized local sites. Methods: Fluorescein isothiocyanate (FITC) or 2, 4‑dinitrofluorobenzene (DNFB) was used as hapten, and migration of FITC + DCs in the dLNs and local recruitment of MHC class II + and CD11c + cells were compared between abdominal skin and VM sensitization by flow cytometric analyses and immunohistochemistry. Expression of tumor growth factor (TGF)‐β at mRNA and protein levels, and local recruitment of CD206 + cells were examined after VM sensitization. Results: VM sensitization showed less numbers of FITC + MHC class II high CD11c + migratory DCs in the dLNs at 6 and 24 h, as compared with skin sensitization. Both skin and VM sensitization induced the recruitment of dermal/submucosal DCs at 6 h, but the number of submucosal DCs in the VM was significantly decreased at 24 h. VM showed persistently higher mRNA levels of TGF‐β2/β3 expression than those of the skin before and after sensitization. In the VM sensitization, increment of CD206 + MHC class II + cells was observed especially at the deep lamina propria at 24 h. Most of CD206 + cells were also positive for the binding to Fc chimeric TGF‐β receptor that interacts with all TGF‐β isoforms, suggesting TGF‐β expression. Conclusion: DC migration to dLNs and localization of DCs at the sensitized sites are limited in the VM sensitization. Our results suggest that the existence of TGF‐β‐expressing CD206 + cells may contribute less sensitization ability and CHS responses in the VM. Abstract : To investigate mechanisms of vaginal mucosa (VM) sensitization in contact hypersensitivity (CHS), we examined migration of hapten‐captured dendritic cells (DCs) in the draining lymph nodes (dLNs) and recruitment of DCs at the sensitized local sites in VM sensitization as compared with skin sensitization. We observed that DC migration to dLNs and localization of DCs at the sensitized sites were limited in the VM sensitization with high TGF‐β expression levels, increment of CD206 + cells, and TGF‐β expression in CD206 + cells in the VM. These results suggested that existence of TGF‐β‐expressing CD206 + cells may contribute less sensitization ability and CHS responses in the VM.